Pendidikan Karakter Islam Prespektif Pemikiran Ahmad Amin dan Relevansinya di Era Modern - Muhammad Habib Zainul Huda; Maragustam Siregar (Moral : Jurnal kajian Pendidikan Islam, 2025)
Character education is a fundamental aspect in the effort to shape individuals with morals, ethics, and responsibility amidst the currents of globalization and modernization. The phenomenon of moral crisis, ethical degradation, and dehumanization emphasizes the urgency of character education that is not only oriented towards intellectual intelligence, but also emphasizes spiritual and social values. In this context, the thoughts of Ahmad Amin, a modern Islamic thinker, are relevant to be re-examined. Ahmad Amin emphasized the importance of Islamic values ​​as a foundation for ethics and morality that are both universal and contextual, thus able to address the needs of modern humans who are facing complex challenges in various aspects of life. This study uses a library research method with a qualitative approach. The main data sources are Ahmad Amin's works related to the concept of morals and education, supplemented by supporting literature discussing character education and its relevance in today's development. The analysis was conducted descriptively and analytically to examine Ahmad Amin's ideas and relate them to the needs of modern society. The results of the study indicate that Ahmad Amin's thoughts on character education are rooted in Islamic moral principles that emphasize the balance between spiritual, intellectual, and social aspects. Values ​​such as honesty, responsibility, discipline, and social awareness are at the heart of healthy character development. This thinking is relevant to the needs of the modern era, marked by a moral crisis, and therefore can serve as an alternative paradigm for character education that adapts to current developments while remaining grounded in Islamic values. Therefore, it can be concluded that Ahmad Amin's thinking is not only of historical value but also makes a significant contribution to developing character education based on Islamic values, capable of maintaining spiritual orientation while addressing the challenges of modernity.